The mediating role of identity status in the relationship between attachment styles and addiction to social media in the high school students - Azadeh Fallah; Yaser Rezapour Mirsaleh; Alireza Pak Gohar (University of Hormozgan, 2022)
The aim of this study was to investigate the mediating role of identity status in the relationship between attachment styles and addiction to social media in high school students in Meybod (Iran). The study method was descriptive-correlational and the statistical population was 1610 male and female high school students of Meybod in 2021. Participants were 310 students whom selected by random cluster sampling (197 girls and 113 boys). Data were collected using Collins and Read Revised Adult Attachment Scale, Waltz etal. Social Media Addiction Questionnaire and Berzonsky Identity Styles Questionnaire. The model was analyzed by structural equation modeling. Results indicated that secure attachment style had a direct and negative effect on addiction to social media (p <0.01), and confused identity had a direct and positive effect on addiction to social media (p <0.01). Also, secure attachment style had an indirect effect on addiction to social media by affecting confused identity (p <0.01). Based on the findings, it can be concluded that confused identity has a significant mediating role in the relationship between secure attachment style and addiction to social media; In other words, secure attachment reduces addiction to social media through confused identity in high school students.